Boosting Vocabulary Through Play: Funbrain’s Impact on SMP Muhammadiyah 6 Students - Suciani, Warfida; Ampa, Andi Tenri; Hambali, Uyunnasirah (FKIP Unismuh Makassar, 2025)
This study investigates the effectiveness of the Funbrain game in enhancing vocabulary achievement among seventh-grade students at SMP Muhammadiyah 6 Makassar. Addressing the urgent need for engaging, technology-based learning tools, a pre-experimental design with pre- and post-tests was employed. A purposive sample of 25 students participated, with data collected through a 20-item multiple-choice vocabulary test. Results revealed a significant improvement in students’ vocabulary scores—from a pre-test mean of 62 to a post-test mean of 83.8. Statistical analysis using a t-test confirmed the significance of this improvement (t-value = 13.6 > t-table = 1.71), leading to the acceptance of the alternative hypothesis (H1) and rejection of the null hypothesis (H0). These findings highlight the potential of educational games like Funbrain to support vocabulary acquisition in EFL contexts, offering a novel and interactive approach to language learning.